Long noncoding RNA LINC-PINT inhibits non-small cell lung cancer progression through sponging miR-218-5p/PDCD4. Issue 1 (4th December 2019) - Zhang, Libin; Hu, Jing; Li, Jiagui; Yang, Qiuju; Hao, Menghui; Bu, Liang
Abstract: Long noncoding RNA, long intergenic non-protein-coding RNA p53-induced transcript (LINC-PINT) was showed to be involved in cancer development. However, the biological effect of LINC-PINT on non-small cell lung cancer (NSCLC) remains unknown. Here, we aimed to investigate the role and underlying mechanism of LINC-PINT in NSCLC. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to measure the level of LINC-PINT in NSCLC tissues and cell lines. Cell counting kit-8 (CCK-8), flow cytometry, migration and transwell invasion assays were used to investigate cell proliferation, cell cycle, cell migration and invasion, respectively. The targets of LINC-PINT were verified by both luciferase reporter assay and RNA immunoprecipitation assay. Tumour xenografts were used to reveal the effect of LINC-PINT on tumourigenesis in vivo . We observed that LINC-PINT expression increased in both NSCLC tissues and cell lines. Function assays exhibited that LINC-PINT reduced NSCLC cell proliferation, cell cycle, cell migration and invasion in vitro . We also indicated that LINC-PINT mediated inhibitory effect on cell proliferation, cell cycle, cell migration and invasion by miR-208a-3p/programmed cell death 4 (PDCD4) in NSCLC cells. These findings indicated that LINC-PINT functions as a tumour-suppressor that exerts important regulatory roles in NSCLC progression by sponging miR-208a-3p/PDCD4.